MODEL PENINGKATAN KINERJA TENAGA PENJUAL : ORIENTASI PELANGGAN, KOMPETENSI TEKNIK TENAGA PENJUAL DAN PERILAKU PENJUALAN ADAPTIF - Sinar Hubtriyan Ade (Jurnal Ekonomi dan Bisnis, 2018)
Adaptive sales behavior that is supported by the competence of salespeople is avariable built in order to bridge the influence between customer orientation on the performanceof salespeople. In this study 102 salespeople at PT. Pelabuhan Indonesia III, (Persero), serve asa research population. The sampling technique used the census method or used the populationas the research sample. This is done looking at the population that is in accordance with theminimum sample requirements in the use of SEM analysis tools (equitio modeling structure)The result of this research proves that customer orientation influence to adaptive sellingbehavior. the technical competence of salespeople influences adaptive sales behavior. Technicalcompetence of salespeople does not affect the performance of salespeople and behavioralsales adaptive effect on the performance of salespeopleKeywords: customer orientation, technical competence of salespeople, adaptive salesbehavior and performance of salespeople